2018
DOI: 10.1002/ep.13015
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization for biodiesel production from Moringa oleifera oil using conch shells as heterogeneous catalyst

Abstract: The potential of conch shells (CSs) as a suitable heterogeneous basic catalyst for transesterification of high FFA content non‐edible Moringa oleifera oil (MOO) was investigated. Biodiesel was produced by a two‐step transesterification process. In the first step, high FFA content of the oil was reduced from 40.25 to 1.4% using reaction conditions of 1:2 v/v methanol to oil ratio, 1.5 vol% H2SO4 concentration, 2 h reaction time and 60°C reaction temperature. In the second step, the esterified oil was converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 75 publications
0
18
0
1
Order By: Relevance
“…The manufacture of biodiesel from Moringa seed oil can also be made with a heterogeneous catalyst that utilizes eggshell and shellfish waste, by first doing the calcination process. After the calcination process, the catalyst particle size will decrease, thus increasing the catalyst surface area [3]. The yield of biodiesel obtained using a shellfish catalyst is 97.06%, which is quite high in biodiesel production Aziz et al [30] compared the use of catalysts from eggshell impregnated with potassium fluoride (KF /eggshell), eggshell, commercial CaO, and commercial CaO impregnated with potassium fluoride (KF /CaO).…”
Section: Heterogeneous Catalyst In Biodiesel Production From Moringa Seed Oilmentioning
confidence: 99%
See 2 more Smart Citations
“…The manufacture of biodiesel from Moringa seed oil can also be made with a heterogeneous catalyst that utilizes eggshell and shellfish waste, by first doing the calcination process. After the calcination process, the catalyst particle size will decrease, thus increasing the catalyst surface area [3]. The yield of biodiesel obtained using a shellfish catalyst is 97.06%, which is quite high in biodiesel production Aziz et al [30] compared the use of catalysts from eggshell impregnated with potassium fluoride (KF /eggshell), eggshell, commercial CaO, and commercial CaO impregnated with potassium fluoride (KF /CaO).…”
Section: Heterogeneous Catalyst In Biodiesel Production From Moringa Seed Oilmentioning
confidence: 99%
“…This is because increasing the methanol content will prevent methanol from reacting with a catalyst which causes difficulty in separating methanol from biodiesel and glycerin. In accordance with the stoichiometric reaction, excess methanol will also push the reaction to the right and increase the conversion, but the use of excess methanol with a long reaction time can cause a glycerolysis reaction [3] and increase the amount of energy when refining biodiesel [28]. The glycerolysis reaction causes glycerol to react with biodiesel to re-form monoglycerides instead of methyl esters [9].…”
Section: Factors Affecting the Transesterification Process Of Moringa Seed Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Subramaniapillai Niju and his colleagues at the PSG College of Technology in India have now found just such a catalyst in the form of conch shells. 1 Other research groups have explored using various shells, including egg shells and oyster shells, as biodiesel catalysts. This is because shells are primarily made from calcium carbonate, and previous research has shown the calcium oxide makes an effective biodiesel catalyst.…”
Section: She Sells Seashells For Biodiesel Productionmentioning
confidence: 99%
“…By tailoring environmental conditions and adding a dash of electricity, Spanish scientists have shown that an unusual class of photosynthetic bacteria can convert the organic material in wastewater into useful biochemicals and hydrogen. 1 In normal photosynthesis, organisms such as plants and cyanobacteria use the energy from visible light to split water into oxygen and hydrogen. This releases electrons, which the organisms use to combine the hydrogen with carbon dioxide to produce various organic compounds.…”
mentioning
confidence: 99%